Creating incentives for innovation? The relationship between pay dispersion in R&D groups and firm innovation performance - Yanadori, Yoshio; Cui, Victor (Strategic Management Journal, 2013)
Innovation is a critical organizational outcome for its potential to generate competitive advantage. While the contribution of knowledge workers to the generation of innovation is widely recognized, little is known about how organizational incentive mechanisms stimulate or inhibit these workers' behaviors that promote innovation. This study examines the relationship between pay dispersion in R&D groups and firm innovation using employee‐level compensation data in US high‐technology firms. The results show that (1) pay dispersion in R&D groups is negatively related to firm innovation and (2) this negative relationship is alleviated in firms with greater financial slack. This study contributes to the innovation literature by illuminating the implications of organizational incentive systems for successful innovation . Copyright © 2013 John Wiley & Sons, Ltd.